The Victim-Offender Overlap in Prison: Examining the Factors Associated With Group Membership - Daquin, Jane C. (Journal of interpersonal violence, 2021)
Historically, criminologists have examined offending and victimization in the community as separate outcomes. Recently, however, researchers have begun to explore the shared commonalities of being an offender and a victim. The victim–offender overlap literature shows that victimization and offending are not different and distinct outcomes, but rather these outcomes share numerous risk factors. A close examination of the victim–offender overlap has not been done within the prison literature. Thus, it remains unclear whether there are commonalities among prisoners who offend while incarcerated and those who experience victimization. The focus of the current study is to (a) identify the proportion of the prisoners who were victims-only, offenders-only, victim–offenders, or neither victim nor offender and (b) identify the factors that predict membership into the four categories of the overlap. The current study used the 2004 Survey of Inmates in State and Federal Correctional Facilities with multinomial logistic regression analyses to examine which factors are associated with group membership into the victim–only, offender–only, or victim–offender groups in prison. Findings show that although the victim–offender overlap exists among prisoners, the majority of prisoners were neither a victim nor an offender. Victim–offenders and victims-only comprise only a small proportion of the sample. Findings also indicate that there are few unique factors across the groups. Results of the study have implications policy and future research.